The organization of industry in the P.R. China: A new start or resort to old concepts? - Wolfgang Klenner (Intereconomics, 1979)
The Chinese have let it be known since the death of Mao Zedong and the purge of the “Gang of Four” that they would in future draw on credits from foreign governments as well as other sources to finance imports of technology. According to western conjectures China's capital requirements may be between US 25 and 50 bn or even a good deal higher. Many observers have taken the view that the Chinese have thereby put all their former development principles behind them. The author of the following article was in the P.R. China about the middle of this year at the invitation of the National Planning Commission. His assessment is that the P.R. China is far from embarking on an entirely new course in its development policy.
Keywords: 330; China